The Effects of Taxes on Income Distribution Justice - Koc, Ozgur Emre; Sarac, Taha Bahadir; Koc, Neslihan; Cicek, Ugur (International Journal of Economics and Financial Issues, 2024)
One of the most important economic problems that countries have faced from the past to the present is income inequality. Income distribution is an important indicator that allows us to understand the social and political structures of societies by revealing how the income gap between the rich and the poor in a country changes. Thus, income redistribution or income justice is one of the important goals of fiscal policy. Taxes are also important intervention tools that economic management has in achieving this goal. In this context, this study aims to examine the relationships between different types of taxes and income distribution in the Turkish economy during the period from 2002 to 2022 by using markov regime switching analysis method. The analysis results indicate that, during the period covered by the study, indirect taxes have a positive effect on income distribution, while taxes based on declaration have a detrimental effect on income distribution.